2014
DOI: 10.1016/j.ijcard.2014.02.042
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of exercise-induced pulmonary arterial hypertension in systemic sclerosis

Abstract: Background: Exercise-induced pulmonary arterial hypertension (EIPH) in systemic sclerosis (SSc) has already been observed but its determinants remain unclear. The aim of this study was to determine the incidence and the determinants of EIPH in SSc. Methods and results: We prospectively enrolled 63 patients with SSc (age 54 ± 3 years, 76% female) followed in CHU Sart-Tilman in Liège. All patients underwent graded semi-supine exercise echocardiography. Systolic pulmonary arterial pressure (sPAP) was derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…Reduced diffusion lung capacity for carbon monoxide (DLCO) and reduced predicted lung volumes seem to predict oxygen desaturation in exercise testing (Someya et al, ). PAH and exercise‐induced PAH are common features in SSc (Gargani et al, ; Saggar et al, ; Suzuki et al, ; Voilliot et al, ). Exercise‐induced PAH is mainly related to increased left ventricular filling pressure and exercise pulmonary vascular resistance (Voilliot et al, ), and may reduce peripheral capillary oxygen saturation ( S pO 2 ) (Yasunobu, Oudiz, Sun, Hansen, & Wasserman, ).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced diffusion lung capacity for carbon monoxide (DLCO) and reduced predicted lung volumes seem to predict oxygen desaturation in exercise testing (Someya et al, ). PAH and exercise‐induced PAH are common features in SSc (Gargani et al, ; Saggar et al, ; Suzuki et al, ; Voilliot et al, ). Exercise‐induced PAH is mainly related to increased left ventricular filling pressure and exercise pulmonary vascular resistance (Voilliot et al, ), and may reduce peripheral capillary oxygen saturation ( S pO 2 ) (Yasunobu, Oudiz, Sun, Hansen, & Wasserman, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in SSc patients showed an excessive increase in PAP during physical exercise, associated not only with increase in pulmonary vascular resistance, but also with left ventricle diastolic dysfunction [11,12]. In previous studies, stress echocardiography has been used mainly to verify whether an exercise echocardiogram could identify SSc patients who may develop PH [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Exercise echocardiography (ExE) has previously been used in the evaluation of patients with scleroderma and in familial forms of pulmonary hypertension [10][11][12]; more recently, Collins and coll. used this technique to evaluate the change in pulmonary artery pressure in patients with systemic lupus erythematous and with limited and diffuse SSc.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, patients with SSc were consecutively selected from the rheumatology database of the University Hospital of Liège from January 2008 to November 2012. 21 All patients signed informed consent, after the University Hospitals Institutional Review Boards approved the study protocol.…”
Section: Patient Selectionmentioning
confidence: 99%
“…Methodological details and baseline characteristics have already been published. 6,21 Bicycle stress echocardiography was performed in a semi-supine position, with the exercise table tilted 20 -308 to the left. Patients started at an initial workload of 25 W, which was increased by 25 W every 2 min, until the maximal tolerated workload.…”
Section: Rest and Bicycle Stress Echocardiographymentioning
confidence: 99%